Deductive Systems of BCK-Algebras - Celani, Sergio Arturo (2004)
In this paper we shall give some results on irreducible deductive systems in BCK-algebras and we shall prove that the set of all deductive systems of a BCK-algebra is a Heyting algebra. As a consequence of this result we shall show that the annihilator F∗ of a deductive system F is the the pseudocomplement of F. These results are more general than that the similar results given by M. Kondo in [7].